Neisseria - Mosab Nouraldein Mohammed Hamad (جامعة الشيخ عبدالله البدري, 2023)
Distinguishing Features: Gram-negative, kidney bean–shaped diplococci Oxidase-positive Large capsule; latex particle agglutination (or CIE, counter immuno-electrophoresis) to identify N. meningitidis capsular antigens in CSF Grows on chocolate (not blood) agar in 5% CO2 atmosphere Ferments maltose in contrast to gonococci